Exploring blood metabolites and thyroid disorders: a bidirectional mendelian randomization study - Zhang, Xuan; Zhou, Jiating; Xie, Zilan; Li, Xi; Hu, Jiaqing; He, Hengzheng; Li, Zhi (Frontiers in Endocrinology, 2023)
Background Human blood metabolites have demonstrated close associations with thyroid disorders in observational studies. However, it's essential to determine whether these correlations imply causation. Mendelian Randomization (MR) offers a promising approach to investigate these patterns.Aims The primary aim of our investigation is to establish causality between blood metabolites and three thyroid disorders: TC, GD, and HT.We employed a two-sample bidirectional MR analysis approach to assess the relationships between 452 blood metabolites and the three aforementioned thyroid disorders. Causal links were estimated using the IVW method, with sensitivity analyses conducted via MR-Egger, Weighted Median, and MR-PRESSO. We assessed potential heterogeneity and pleiotropy using MR-Egger intercept and Cochran's Q statistic.Additionally, we conducted pathway analysis to identify potential metabolic pathways.We found 46 metabolites that showed suggestive associations with thyroid disease risk, especially，Aspartate (ORIVW=7.41; 95%CI: 1.51-36.27; PIVW=0.013) and C-glycosyltryptophan (ORIVW=0.04; 95%CI: 0.00-0.29; PIVW=0.001) impacted TC,